Implantação do prontuário eletrônico na Atenção Primária no Sistema Único de Saúde: resultado do PMAQ AB 2011 e 2014 - Raphaella do Amaral Velloso (2019)
The permanent construction of the Brazilian public health system, which is public, universal, integral and free, is a challenge for the Brazilian nation, for the Ministry of Health (MS) and for all organs responsible for health in the three spheres of government. As a way to assist in this construction, public health policies were created to improve this system and make it more efficient and effective in the health care of the population. The health information systems in Brazil have the function of subsidizing the process of permanent evaluation of the health situation of the population and of the results of the implemented health actions, providing elements to adapt these actions to the objectives of the Unified Health System (SUS) . The informatization of the electronic medical record is a policy that has been charged by the Ministry of Health and aims at standardizing the patient's medical records, integrating the health information network at all levels of care, providing and streamlining information consultation, obtaining reliable data about the needs the health of the population and to obtain useful information for planning and monitoring actions. The present study aimed to describe the evolution of the electronic health record (EHR) implantation process in primary care of the Unified Health System (SUS) in Brazilian municipalities in 2011 and 2014 following the National Program for Access and Quality Improvement in Primary Care (PMAQ AB).A quantitative crosssectional descriptive and analytical study was performed. The results of the external evaluation of the 1st and 2nd cycles of the PMAQ AB of 2011 and 2014 were used. The sample consisted of 3836 Brazilian municipalities that took part in both cycles. In the data analysis, the EHR implantation was a dependent variable. The independent variables were: the level of implantation reached in 2011, 2014; if the electronic health record is integrated with other care units of the network; and different implantation situations depending on the country region.The EHR implantation process in Brazil demonstrated a significant increase between 2011 and 2014, however, the implantation percentage is still very low in both years. The process is uneven in different regions of the country, with North and Northeast regions showing the worst results in three evaluated questions and the South and Southeast regionsthe best. When the new politics like the one of informatization of the patient records are developed, the principle of fairness shall be taken into account. It is important to emphasize the concern with electronic health record data privacy and reliability.